Benzo[a]pyrene exacerbates allergen-induced airway inflammation through NLRP3-dependent dendritic cell activation and pathogenic T helper cell polarization - Zou, Huamei; Duan, Jiaqi; Xie, Yongmin; Chen, Ruien; Ye, Yanyu; Zhang, Aizhi; Yang, Pingchang; Yang, Gui; Liu, Xiaoyu (Frontiers in Immunology, 2025)
BackgroundEnvironmental pollutants are known to aggravate allergic diseases, but the molecular mechanisms by which polycyclic aromatic hydrocarbons such as benzo[a]pyrene (BaP) potentiate allergic airway inflammation remain poorly understood.ObjectiveWe investigated how BaP co-exposure modifies house dust mite (HDM)–driven allergic airway responses, focusing on the role of the NLRP3 inflammasome in dendritic cells (DCs).MethodsMice were sensitized and challenged intranasally with HDM with or without BaP. Airway hyperresponsiveness (AHR), bronchoalveolar lavage (BAL) cell counts, lung histopathology, and serum HDM-specific IgE were assessed. Cytokine production and epithelial alarmins were measured by ELISA. The role of NLRP3 was evaluated using Nlrp3−/− mice, in vitro bone marrow–derived DC (BMDC) cultures, and adoptive transfer of lung DCs. T helper cell polarization was analyzed in OT-II co-culture assays.ResultsCo-exposure to BaP and HDM markedly exacerbated airway inflammation, with enhanced AHR, increased eosinophil and neutrophil infiltration, severe goblet cell hyperplasia, and elevated HDM-specific IgE. Cytokine analysis revealed synergistic induction of Th2 (IL-4, IL-5, IL-13) and Th17 (IL-17A) responses, alongside increased epithelial alarmins (TSLP, IL-33). This exacerbated phenotype was abolished in Nlrp3−/− mice, which failed to produce IL-1β/IL-18 and exhibited attenuated inflammation. In vitro, BaP synergized with HDM to activate NLRP3 in BMDCs, leading to caspase-1 cleavage, IL-1β release, and enhanced CD80/CD86 expression. Adoptive transfer of BaP/HDM-exposed WT lung DCs, but not Nlrp3−/− DCs, was sufficient to drive allergic airway inflammation in naïve recipients. Finally, BaP–conditioned WT DCs skewed naïve CD4+ T cells toward Th2 and Th17 lineages, an effect absent in Nlrp3−/− DCs.ConclusionBaP amplifies allergic airway disease by activating the NLRP3 inflammasome in DCs, thereby enhancing DC maturation, cytokine release, and pathogenic Th2/Th17 polarization. These findings identify a critical mechanism linking environmental pollutants to exacerbated allergic asthma and highlight the NLRP3 inflammasome as a potential therapeutic target.